Masculinity, Autocracy and the Russian University, 1804-1863 - Friedman, R. author. aut Link
X, 195 p.
Keywords: This is the first book-length study of masculinity in Imperial Russia. By looking at official and unofficial life at universities across the Russian empire, this project offers a picture of the complex processes through which gender ideologies were forged and negotiated in the Nineteenth Century. Masculinity, Autocracy and the Russian University, 1804-1863 demonstrates how gender was critical to political life in a European monarchy.